DEVELOPING MODEL MANAGEMENT OF SPECIAL EMPLOYMENT UNIT (BKK) OF SMK AS SMK GRADUATES MARKETING (Universitas Negeri Semarang, 2014)
Vocational High School (SMK) is a type of secondary education that specifically prepares its graduates to become skilled and trained workers. Therefore, there is an urgency to provide a marketing service for the graduates through a special employement unit (BKK). This study discusses the development of a BKK management model in SMK. The preparation of BKK model design began with the field study to obtain factual condition in the field. This research was conducted using of Research and Development (R & D) method. This study was set in four vocational schools which had BKK. The four study sites were in SMK N 4 Semarang BKK, SMK N 6 Semarang BKK, SMK N 8 Semarang BKK, SMK N 9 Semarang BKK, as well as the representatives of industrial market in Central Java. The steps of the model in this study include (1) a factual analysis models of Special employement unit (BKK), (2) development of a conceptual model, (3) the needs analysis of BKK, (4) the development of a hypothetical model, (5) the development of a final model. The results show that the factual conditions in SMK BKK do not exhibit any optimal progress, especially dealing with their duties in marketing the SMK graduates. The aspect of finance greatly affects the implementation of SMK BKK. BKK Model Management in SMK is expected to overcome the problems encountered in the area of BKK